Exploring the Dominance of Pull and Push Forces and Role of Geography towards Non-Farm Employment in Rural Tamil Nadu, India - Balaji, S.J. (Indian Journal of Extension Education, 2023)
The present study attempts to study the trend, distribution and determinants of nonfarm employment in rural Tamil Nadu using household level information provided in NSS-Employment Survey for the year 2011-12. It employs Getis-Ord’s index of spatial correlation to study the employment distribution across sub-units of the state, and logistic regression to study the extent of influence of different pull and push forces that attract/detract individuals engaging into nonfarm occupations. Results obtained show that the state stands second among southern states employing around two-fifth of rural labor in nonfarm occupations, but labor absorption has slowed down since mid-1990s. Cross-sectional estimates show that nonfarm labor shares are high in just one-sixth of all districts, and employment levels are low in 40 percent of the districts. low labor-share districts are at eastern region. To the other end, medium labor-share districts are primarily located at western and northern region of the state. While southern districts show us a mixed pattern, districts with more than 60 percent nonfarm labor-share are scattered across the state. Maps of Getis-Ord’s statistic show ‘cold spot’ cluster, providing evidence favoring spatial clustering in low employment regions. Among determinants, higher education and training stands matter the most in accessing to nonfarm occupations. Odds-ratio of logistic regression show that persons with a literacy level of graduation and above are 18 times more likely to access nonfarm jobs, whereas persons having vocational training are around 4 times more likely to obtain nonfarm jobs. Interestingly, agricultural productivity, and farm-nonfarm wage ratio had no significant influence on accessing nonfarm jobs.